2007
DOI: 10.1523/jneurosci.1063-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Disambiguation of Overlapping Experiences by Neurons in the Medial Entorhinal Cortex

Abstract: Hippocampal neuronal activity distinguishes separate events that share common elements. Here, we examined whether the capacity to disambiguate overlapping experiences is an exclusive feature of hippocampal processing or whether information processing one stage earlier in the hippocampal system also disambiguates common elements of distinct experiences. We compared the spatial firing patterns of neurons in the dorsocaudal medial entorhinal cortex (dcMEC) and hippocampal CA1 neurons in animals continuously alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
88
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 41 publications
(65 reference statements)
14
88
1
Order By: Relevance
“…Is it possible that the MEC, like the parahippocampal cortex, also plays a broader role in temporal as well as spatial contextual processing? Results of a recent study by the present authors are consistent with this suggestion (Lipton et al, 2007). In this study, our aim was to determine whether MEC neurons, like hippocampal principal cells, distinguish routes traversed as temporally distinct episodes during performance of a T-maze alternation task.…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediasupporting
confidence: 84%
See 4 more Smart Citations
“…Is it possible that the MEC, like the parahippocampal cortex, also plays a broader role in temporal as well as spatial contextual processing? Results of a recent study by the present authors are consistent with this suggestion (Lipton et al, 2007). In this study, our aim was to determine whether MEC neurons, like hippocampal principal cells, distinguish routes traversed as temporally distinct episodes during performance of a T-maze alternation task.…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediasupporting
confidence: 84%
“…It should be noted that in another study nearly all hippocampal neurons differentiated left-and right-turn trial types . However, in the current discussed situation in which the differentiation of trial types was weaker in hippocampal neurons (Lipton et al, 2007), MEC neurons showed stronger disambiguation. The combination of these and other analyses showed that both MEC and hippocampal neurons had significant spatial specificity and distinguished leftand right-turn trials.…”
Section: The Role Of the Parahippocampal/ Postrhinal Cortex And Mediacontrasting
confidence: 61%
See 3 more Smart Citations